1999
DOI: 10.1046/j.1469-8137.1999.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of visualization techniques for recording arbuscular mycorrhizal colonization

Abstract: The extent of arbuscular mycorrhizal colonization was assessed in 10 field-collected plant species, representing three annual forbs, three perennial forbs, three perennial grasses and one annual grass. Each root system of each plant was split into four portions, and for each portion, mycorrhizal structures were revealed with epifluorescence microscopy (under which only arbuscules are generally visible) and three commonly used stains (Chlorazol Black E, Acid Fuchsin and Trypan Blue). The aim of the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 21 publications
1
45
1
Order By: Relevance
“…To check for mycorrhizal colonization they were placed on a microscope slide and examined at´200 using a Zeiss Axiophott epiuorescence microscope ®tted with a UV lamp and ®lters giving a transmission of 455±490 nm blue. Under these conditions, the arbuscules¯uoresce (Ames et al 1982) and it has recently been shown that this is a more reliable and consistent method of mycorrhizal visualization than conventional staining methods (Gange et al, 1999). At the 12-week stage, all inoculated plants showed a degree of colonization, while no mycorrhiza was found in any plant given irradiated inoculum (hereafter referred to as`control' plants).…”
Section: Methodsmentioning
confidence: 98%
“…To check for mycorrhizal colonization they were placed on a microscope slide and examined at´200 using a Zeiss Axiophott epiuorescence microscope ®tted with a UV lamp and ®lters giving a transmission of 455±490 nm blue. Under these conditions, the arbuscules¯uoresce (Ames et al 1982) and it has recently been shown that this is a more reliable and consistent method of mycorrhizal visualization than conventional staining methods (Gange et al, 1999). At the 12-week stage, all inoculated plants showed a degree of colonization, while no mycorrhiza was found in any plant given irradiated inoculum (hereafter referred to as`control' plants).…”
Section: Methodsmentioning
confidence: 98%
“…(e) Examine the roots under the microscope at ×100 magnification. The degree of mycorrhizal colonisation varies depending on staining agent and plant species (Gange et al 1999).…”
Section: Storing Processing and Observations (Categories 1-4)mentioning
confidence: 99%
“…The cassettes were washed under tap water, immersed in 3% HCl for 2 min, and washed under running tap water and then with deionized distilled water. The roots were removed from the cassettes and stained with 0.05% trypan blue (Sigma-Aldrich, St. Louis, MO) in deionized distilled water, glycerol, and lactic acid (1:1:1) solution (Cao et al 2013;Gange et al 1999). The stained roots were observed under a Leica DM750 microscope (40× ; Leica Microsystems, Concord, ON), and mycorrhizal colonization and percent arbuscule and vesicle abundance were measured using the scoring procedure described by Trouvelot et al (1986).…”
Section: Sms Treatmentsmentioning
confidence: 99%